Neurophysiological basis of a new electrode configuration to potentiate the tDCS: Protocols for upper limbs - Cavalcanti, João Zugaib; Gomes, Iago Oliveira; Baptista, Abrahão Fontes; Sá, Katia Nunes; Matos, Marcos Almeida; de Lucena, Rita de Cássia Saldanha (Revista Pesquisa em Fisioterapia, 2017)
Transcranial Direct Current Stimulation (tDCS) uses a direct electrical current to modulate the activity of cortical neurons. Anodal tDCS (positive pole) increases the excitability of cortical neurons, while cathodic tDCS (negative pole) reduces it. However, when applied in the peripheral nervous system the effects are the opposite of cranial application. Furthermore, when central and peripheral stimuli are used concomitantly, their effects can be summed up. This has been demonstrated by combining tDCS with other forms of sensory peripheral stimulation. We propose a new electrode configuration to potentiate the excitatory and inhibitory effects of tDCS on neuronal excitability and increase upper limb motor function. Our hypothesis is that placement of the electrodes in the primary motor cortex (M1) and the contralateral brachial plexus (BP) would promote this potentiation by central and peripheral synaptic summation. We will test our hypothesis in two proof-of-concept studies. Study 1) Secondary trial, in which we will evaluate the effects of these configurations on the neuronal excitability of healthy individuals; Study 2) A double-blind, randomized and crossover clinical trial in which we will test the stimulation with the anode in M1 and the cathode in the contralateral BP on the motor function and electrophysiological markers of individuals with cerebral palsy. The effects of the new configurations will be compared with the conventional configuration (M1 / contralateral supraorbital region). We expect that our investigations will identify a more efficient way to apply tDCS and consequently a better clinical use of this technique.